Genetic improvement of local cattle breeds in West Africa: A review of breeding programs - Ouédraogo, D.; Soudré, A.; Yougbaré, B.; Ouédraogo-Koné, S.; Zoma‑Traoré, B.; Khayatzadeh, N.; Traoré, A.; Sanou, M.; Mészáros, Gábor; Burger, P.A.; Okeyo Mwai, Ally; Wurzinger, Maria; et al. (MDPI, 2021)
Cattle are one of the most important livestock species in West Africa, providing multiple services to farmers and contributing to national economies. Various breeding strategies have been implemented to enhance their productivity and have improved farmer livelihoods. This review describes cattle breeding experiences across West Africa, spanning the N’Dama breed in Mali, Senegal, and The Gambia to the breeds Azawak Zebu, Fulani Zebu, and taurine Baoulé in Burkina Faso. The main objectives of most breeding programs have been to optimize meat and milk performance of taurine and Zebu cattle as well as trypanotolerance of taurine cattle. In some cases, “closed nucleus” schemes have proven limited and so have evolved into “open nucleus” schemes. Recent community-based breeding programs have shown promise. The major challenges of breeding programs remain defining realistic breeding objectives and securing the involvement of stakeholders. All the strategies reviewed here have been funded externally within development or research projects that are often too short to yield tangible genetic improvement, and whether they will continue beyond those projects is uncertain. This review highlights the need for continuing government support to ensure the sustainability of local cattle breeding programs.